2017
DOI: 10.1016/j.atherosclerosis.2017.02.021
|View full text |Cite
|
Sign up to set email alerts
|

PKC-epsilon and TLR4 synergistically regulate resistin-mediated inflammation in human macrophages

Abstract: Background and aims Resistin has been associated with atherosclerotic inflammation and cardiovascular complications. We and others have previously shown that PKC-epsilon (PKCε) is involved in resistin-induced smooth muscle cell (VSMC) dysfunction at a high pathological concentration. This study aimed to evaluate the role and potential pathways of resistin at a physiological concentration, in atherosclerosis-related inflammation. Methods Plasma from patients with atherosclerosis was analyzed for resistin conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 48 publications
2
36
0
1
Order By: Relevance
“…It is clear from the literature that resistin activates NFκB signaling. Such activation has been demonstrated in the HepG2 cells 36 , human coronary artery endothelial cells 38 and in human macrophages 37 . Importantly, genetic approaches have now established the classical NFκB pathway as a negative regulator of myogenesis.…”
Section: Discussionmentioning
confidence: 82%
“…It is clear from the literature that resistin activates NFκB signaling. Such activation has been demonstrated in the HepG2 cells 36 , human coronary artery endothelial cells 38 and in human macrophages 37 . Importantly, genetic approaches have now established the classical NFκB pathway as a negative regulator of myogenesis.…”
Section: Discussionmentioning
confidence: 82%
“…There are few other reports identifying CAP1 as a bonafide receptor for resistin (Lee et al, ; Munjas et al, ). In contrast, TLR4 appears to be a more widely studied receptor of resistin, in not just human cancer models (Gong et al, ; Wang et al, ) but various disease models as well (Y. Jiang et al, ; Li et al, ; Miao et al, ; Zuniga et al, ). Based on the relative number of reports vouching for these two receptors to be the receptors for resistin, clearly TLR4 seems to be relatively well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that RETN is associated with type 2 diabetes [ 30 , 31 ], which indicates that RETN could be involved in the host immune response process. It has been reported that RETN can induce production of pro-inflammatory cytokines and chemokines in PBMCs and, can promote macrophage polarization in an independent process [ 32 34 ]. In our study, we found that RETN expression was significantly increased in active TB patients compared to LTBI and HC individuals.…”
Section: Discussionmentioning
confidence: 99%